The Cultivation of Wonder in the Premedical Learning Environment: Nurturing Ethical Character in the Early Formation of Health Professionals. Issue 3 (3rd July 2018) - Geller, Gail; Caldwell, Meredith; Merritt, Maria W.
Abstract: The learning environment of premedical education on many American undergraduate campuses appears to be relentlessly competitive, potentially undermining virtues of moral character critical to success in medical school and to eventual clinical excellence. We propose a new line of inquiry exploring the "capacity for wonder, " the propensity to encounter everyday experiences with a sense of radical appreciation, as a personal disposition that, if cultivated in the premedical learning environment, may support the development of six specific virtues among future medical students: courage, curiosity, humility, gratitude, respect, and compassion.